Analisis Wacana Kritis Model Teun A.Van Dijk pada Surat Kabar Online dengan Tajuk Kilas Balik Pembelajaran Jarak Jauh Akibat Pandemi Covid-19 - Mukhlis, Muhammad; Masjid, Akbar Al; Widyaningrum, Heny Kusuma; Komariah, Kokom; Sumarlam, Sumarlam (GERAM: Gerakan Aktif Menulis, 2020)
This study aimed to describe the Teun A Van Dijk's model text's dimensions in online news text discourse on Kompas.com Newspaper with the headline "Flashback to Distance Learning due to the Covid-19 Pandemic" on September 3, 2020. This study's data were speech and dialogue on the online media kompas.com, while the data source for the online newspaper kompas.com is in the form of news texts about distance learning flashbacks due to the Covid-19 pandemic. Data The data collection methods and techniques used the documentation method with the observation and note technique. In contrast, the data analysis method used the content analysis method with the Teun A Van Dijk model of critical discourse analysis approach. The results of this study indicate that the dimensions of Teun A Van Dijk's text consist of three parts, namely the superstructure, macro-structure, and microstructure measurements. The superstructure dimension is about coherence and schematic of text. The macrostructure dimension discusses thematic/topics, namely examining flashbacks or evaluating the implementation of the distance learning policy announced by the Indonesian Minister of Education and Culture. The measurements of the microstructure that found in background elements, details, intentions, presuppositions, sentence form (passive and active sentences), coherence (additive/addition coherence, causal coherence, and contrast coherence), pronouns (their pronouns and us), lexicon, graphics, and metaphors (figure of speech).